Skin Microbiota Variation Among Bat Species in China and Their Potential Defense Against Pathogens - Li, Zhongle; Li, Aoqiang; Dai, Wentao; Leng, Haixia; Liu, Sen; Jin, Longru; Sun, Keping; Feng, Jiang (Frontiers in Microbiology, 2022)
Host-associated skin bacteria are essential for resisting pathogen infections and maintaining health, including the deadly fungal pathogen Pseudogymnoascus destructans in North America. Bats in Asia were also infected with P. destructans but no obvious disease symptoms. However, we have little understanding of how chiropteran skin microbiota are distributed among bat species and their habitats, or of their putative roles in defending against P. destructans in Asia. In this study, we characterized the skin microbiomes of four bat species at five localities using 16S rRNA gene amplicon sequencing to understand their skin microbial composition, structure, and putative relationship with disease. The alpha- and beta-diversities of skin microbiota differed significantly among the bat species, and the differences were affected by environmental temperature, sampling sites, and host body condition. The chiropteran skin microbial communities were enriched in bacterial taxa that had low relative abundances in the environment. Most of the potential functions of skin microbiota in bat species were associated with metabolism. Focusing on their functions of defense against pathogens, we found that skin microbiota could metabolize a variety of active substances that could be potentially used to fight P. destructans. The skin microbial communities of bats in China are related to the environment and the bat host, and may be involved in the host’s defense against pathogens.